Venture distress and problemistic search among entrepreneurs in Brazilian favelas - Lenz, Anna-Katharina; Sutter, Christopher; Goldszmidt, Rafael; Zucco, Cesar (Journal of Business Venturing, 2021)
When do entrepreneurs in emerging markets seek out help from organizational sponsors? Problemistic search theory suggests that entrepreneurs will seek out sponsors in moments of venture distress. However, this theory was developed in the context of large organizations; it is not clear how it might apply to entrepreneurs in resource-constrained contexts. We use three inductive studies conducted in favelas in Brazil to examine when entrepreneurs seek help. Consistent with problemistic search theory, we find evidence that entrepreneurs seek out help from organizational sponsors in moments of venture distress. We also explore what types of entrepreneurs are most likely to seek help in a situation of venture distress and find that entrepreneurs who are more socially embedded and have more social obligations are more likely to take up sponsorship services, leading to important heterogeneity in our results on take-up. We find that women, more mature ventures, and middle-aged entrepreneurs are all more likely to engage in problemistic search. We contribute to a more contextualized theory of problemistic search for small entrepreneurs in emerging markets. We also provide important theoretical and practical insights about the demand-side of organizational sponsorship.